EFEKTIFITAS PERATURAN MENTERI LINGKUNGAN HIDUP DAN KEHUTANAN REPUBLIK INDONESIA NOMOR 68 TAHUN 2016 TENTANG BAKU MUTU LIMBAH DOMESTIK DI KABUPATEN BADUNG - I Wayan Bramantha Junior Saga Dirga; Anak Agung Adi Lestari (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
he issuance of Minister of Environment and Forestry Regulation No. 68 of 2016 concerning Domestic Wastewater Quality Standards is a government effort in enforcing and supervising the disposal and treatment of domestic wastewater where domestic liquid waste is waste which is always a very significant problem if it is not handled properly. . Badung Regency is one of the tourist areas that has a dense population, as well as business entities that have been established specifically to support the tourism sector. In this case the problem of domestic wastewater arises from business entities and community settlements that are not properly disposed of and managed in accordance with applicable regulations which will have a negative impact on the environment and health. The problem studied in this thesis is how effective domestic wastewater treatment is in Badung Regency and the supporting factors for the obstacles faced by the environmental and sanitation services in tackling violations in the treatment and disposal of domestic wastewater in Badung Regency.